Akuntabilitas Sistem Informasi Manajemen Nikah (SIMKAH) dalam Implementasi Undang-Undang Perkawinan di Kantor Urusan Agama - M Tohir; Umar Zakka; Mahtumridho Gufron Bin Simun (AL - IBRAH, 2025)
This study evaluates the accountability of the Nikah Management Information System (SIMKAH) in the implementation of the Marriage Law at the Office of Religious Affairs (KUA). Using a qualitative approach with a case study design, this research assesses the role of SIMKAH in improving the efficiency, accuracy and transparency of marriage administration. Data were collected through in-depth interviews, observation, and document analysis. Analysis was conducted thematically, through four main stages: data reduction, coding, theme grouping, and thematic description to identify patterns relating to SIMKAH accountability. The results showed that SIMKAH strengthens KUA accountability by speeding up the recording process, reducing errors, and improving access to information for related parties. However, some constraints such as limited technological infrastructure and lack of user understanding are still a challenge. This study recommends increased training for staff and strengthening technological infrastructure to optimise SIMKAH implementation. The findings provide important insights for the government in developing a more accountable and transparent marriage administration system in Indonesia.